The attitude of the citizens of Bosnia and Herzegovina towards misinformation during the coronavirus pandemic with regard to the level of education - Trninić, Dragana; Bokan, Jovana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
Despite the fact that disinformation exists beyond the mass media, space in the media sphere, especially the virtual one, leaves the possibility that disinformation can spread easier and faster, as well as reach a large audience of users of social networks, ie. digital media. With the arrival of the coronavirus, there was a greater need for information, but at the same time the amount of misinformation from various intentions and sources increased. The development of information and communication technologies, ways of communicating and disseminating media content, on the other hand, is in stark contrast to the process of developing media education in Bosnia and Herzegovina and the level of media literacy of citizens who are not ready for new ways of communicating, sources of information and the procedure of participation in the creation of media content. In Bosnia and Herzegovina, media education is not part of the compulsory education system and because of that in this paper we will talk about the attitude of citizens towards misinformation during the coronavirus pandemic, given the level of their general education with the aim of determining whether the level of general education affects the power of perception of misinformation. The results of research conducted by a qualitative method through a focus group and presented by thematic analysis indicate a cause-and-effect relationship between levels of general education and perceptions of misinformation. The final conclusion is that the higher the level of general education means the higher the level of media competencies for deconstructing misinformation and resistance to such content.
Keywords: misinformation, pandemic, coronavirus, media literacy, education.